Beyond traditional screening: Unveiling antibiotic potentials of actinomycetes in extreme environments - Lyudmila P. Trenozhnikova; Gul B. Baimakhanova; Baiken B. Baimakhanova; Assya S. Balgimbayeva; Saule T. Daugaliyeva; Elmira R. Faizulina; Larisa G. Tatarkina; Gulzhan A. Spankulova; Dmitriy A. Berillo; John A. Beutler (Heliyon)
Extreme ecosystems are a rich source of specialized metabolites that can overcome multidrug resistance. However, the low efficiency of traditional exploratory research in discovering new antibiotics remains a major limitation. We hypothesized that actinomycetes may have the ability to produce antibiotics in the extremes of a changing natural environment. This study introduces a novel approach to screening natural antibiotic producers from extreme habitats based on the relationship between organisms' adaptive traits and their metabolic activities. The antibacterial and antifungal properties of 667 actinomycete isolates, obtained from 160 samples of Kazakhstan's diverse extreme habitats, were studied under neutral, saline, and alkaline conditions against MRSA, E. coli, C. albicans, and A. niger. Among these isolates, 113 exhibited antibacterial properties, and 109 demonstrated antifungal properties. Notably, one-fifth of the antagonist isolates could produce active substances solely under extreme growth conditions. Fifty-three antagonistic actinomycetes, possessing these characteristics, have been categorized into groups and warrant further investigation as potential producers of new natural antibiotics. Molecular genetic analysis of the selected isolates revealed a high prevalence of Streptomyces and Nocardiopsis strains. Furthermore, 83.4 % of obtained isolates demonstrated the ability to thrive in all studied habitats—neutral, saline, and alkaline. 96.3 % of actinomycetes isolated from extreme environments exhibited adaptation to neutral conditions, highlighting their inherent versatility. Our findings underscore the nearly complete potential (99.7 %) of isolates to overcome the salinity barrier of 3.5 % NaCl, indicating their capacity to inhabit oceanic environments. We assert that actinomycetes should be perceived as a cohesive, globally adaptive group, capable of migrating between changing conditions or remaining stable within them. These studies lay the groundwork for the development of a new platform for screening natural antibiotics.